Assessment of Neuron Specific Enolase Level and some Related Biochemical Factors in Patients with Diabetic Peripheral Nerve Disorders (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: the disorder of neuron system by the action of hyperglycemia is Diabetic neuropathyconsiders a common diabetic complication which is associated with a wide scope of clinical cases. Peripheralneuropathy (PN) represents a clinical case, wherein the peripheral nervous system is damaged. Accordingly,biochemical parameters have importance to apply as good predictor factors. Accordingly we attempt toassess the biochemical factors of Neuron Specific Enolase NSE, Calpotectin CALP, Xanthine Oxidase XODin patients suffering from this type of diabetes complications as early predictors and study their correlations.Methods: Fifty eight patients are known to have diabetic mellitus, which is classified into three groups.Group I represents DPN of 30 patients, group II referred to 28 diabetic patients without DPN, in additionto 30 healthy subjects as a control group, with range age (38-70) years old. BMI was determined for all thestudied groups. Levels of FBS, lipid categories and HbA1C were estimated. NSE, CALP and XOD levelswere measured by ELISA method. hs-CRP also determine for patients and control.Results: The results revealed that levels of both FBS and HbA1C are increased significantly (p
Keywords: Neuron Specific Enolase, Calprotectin, Xanthine Oxidase, diabetic neuropathy